Hubungan Keterpaparan Sumber Informasi Dengan Pengetahuan Remaja Tentang Hiv/Aids Pada Siswa SMA Negeri 01 Karanganyar Demak - Viona, Sepia Tresia; Wahyuni, Sri; Sulistyaningsih, Dwi Retno; Indah Sri Wahyuningsih (An-Najat, 2025)
HIV/AIDS is a serious health problem in Central Java, with 39,978 sufferers, and exposure to information that affects people's lives. Research Objective: To determine the relationship between exposure to information sources and adolescent knowledge about HIV/AIDS in class XI students at SMAN 01 Karanganyar Demak. Method: Quantitative research with a cross sectional approach, using probability sampling with 185 respondents. The inclusion criteria are 1) active as a class XI student at SMAN 01 Karanganyar Demak 2) Willing to be a respondent. The data collection method uses a knowledge questionnaire and exposure to information sources. The data analysis used was univariate analysis and bivariate analysis (Spearman test). Results: The majority of respondents were female (54.6%) and aged 17 years (76.8%). Information exposure was mostly moderate (51.4%), and knowledge about HIV/AIDS was mostly poor (53.5%). There is a significant relationship between exposure to information and knowledge, with a p-value of 0.000. Conclusion: The higher the exposure to information sources, the better the knowledge of adolescents about HIV/AIDS. This research shows the importance of disseminating information to increase public awarenes